PENGARUH MANAJEMEN PENGETAHUAN (KNOWLEDGE MANAGEMENT) TERHADAP KINERJA PENGELOLAAN KEUANGAN DESA MELALUI KOMPETENSI PENGELOLA : (STUDI DI KABUPATEN GUNUNG MAS DAN KABUPATEN PULANG PISAU) - Aminudin Aminudin (Universitas Palangka Raya, 2020)
Shape a village governance professionals, efficient and effective, open and accountable as stipulated in Law No. 6 Year 2014 about the village, then the village financial management must be based on the principles: transparency, accountability, participation and orderly of disciplined budget. Therefore, one of the critical success factor in the management of village finances, highly dependent on the knowledge and competence of human resources involved. This study aims to analyze and explain empirically Effect of Knowledge Management of the Financial Management Performance village with the competences of the variable.The method used in this research is descriptive-quantitative approach. The unit of analysis of this research is all village, Village Consultative Body and the parties related to the financial manager villages are represented, with the category of village developed, developing or underdeveloped in Pulang Pisau and Gunung Mas, the total sample size of 30 people in the category advanced villages and 30 samples in the category of developing rural / under developed. Engineering samples are simple random. Data were analyzed using analysis approach Structural Equation Modeling (SEM) with a moderating effect, the software used is SmartPLS Versi3.Results from the study showed the Knowledge Management strong and positive influence on the competence of financial management in rural village forward and backward villages / evolved. Proven competence business as intermediate or intervening variable. In the village forward, the effect of knowledge management can improve competence and competence to improve the performance of financial operators, while in the backward villages / developing knowledge management influence on competence and does not affect the performance of the financial manager of the village. Performance Financial Management in the village developed significantly different from the performance of Financial Management in the village underdeveloped / developing. Knowledge management has no effect on the performance of financial management in both rural villages developed and underdeveloped villages / evolved.